A domestic rooftop PV system: a step towards retrofitting the built environment to combat climate change in Bahrain - Alnaser, Naser W. (Frontiers in Built Environment, 2023)
This paper assesses the technological, economic and environmental of installing a PV rooftop system on a domestic house in the kingdom of Bahrain from 20th March 2018 until 31st March 2020. The maximum solar electricity generated from this first domestic building in Bahrain in a month was 1,228.9 kWh (August 2018) and the least was 728.16 kWh (December 2019). The maximum Specific Yield (SY) obtained, in a particular day, in two years, was 6.12 kWh/kWp (on 14 April 2019). The annual average of Specific Yield for this domestic building is 4.13 kWh/kWp/day. The average Performance Ratio (PR) of the PV system in 2019 was 73.0 %. The Self Sufficiency (SS) for this installation was found to vary from 15.3% to 50.7%. The average SS value for this house in 2018 was 22.8% while in 2019 was 28.6%. Furthermore, a cubic relation correlation was established, relating the month number (X) and the monthly average of daily Specific Yield (Y). The correlation coefficients were r = 0.85 and R2 = 0.73, with significance P ˂ 0.001. It is found, herein, that installing such PV system in a domestic house will cut, annually, about 39.0 % of CO2 which is equal to 4.637 ton and hence saves 38,567 ft3 of natural gas. This initiative in Bahrain is a step towards retrofitting the built environment to combat climate change.